Institutional Resilience and Cultural Capital: A Systematic Literature Review of Islamic Education Under Mongol Rule - Nisrina Huwaida Qurrottu'Aini; Mutohharun Jinan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
The Mongol expansion in the thirteenth century, culminating in the fall of Baghdad in 1258 under Hulagu Khan, is often associated with the destruction of Islamic intellectual institutions. However, developments during the Ilkhanid period in Persia (1256–1335) reveal a more complex process in which Islamic education was reorganized rather than eliminated. This study examines how Islamic educational institutions adapted and sustained their authority under Mongol rule by analyzing patterns of institutional reconstruction, scholarly agency, and curriculum continuity. Using a narrative literature review approach, this research synthesizes historical and sociological studies, organizing them around themes of political transformation, madrasa development, and cultural capital reproduction. The findings show that although early conquests dismantled major centers such as Bayt al-Hikmah, later Ilkhanid patronage especially after the Islamization of Mongol rulers encouraged the reestablishment of madrasas, strengthened waqf-based funding, and supported scientific inquiry. Figures such as Nasir al-Din al-Tusi illustrate how ulama negotiated political authority while maintaining intellectual production. Drawing on Pierre Bourdieu’s concept of cultural capital, this study argues that madrasas functioned as sites of cultural reproduction, ensuring epistemic continuity amid political rupture.